Mathematical Modelling of the Merging of Turbulent Plumes with Applications to Heat Pump Efflux - Delboyer, Alistair (2022)
In this thesis, the impact of open loop heat pumps on rivers is investigated. These heat pumps inject water of a different temperature into the environment as part of their heating (or cooling) process. In doing so, thermal plumes are created. The behaviour of these thermal plumes is studied using thermal imagery from the Matapédia river and a relationship between the temperature difference between the plume and the downstream distance from the source of the plume is determined.